Assessing Teacher Readiness for Merdeka Curriculum Implementation: A Case Study in Bulukumba Regency - Rosmita Rosmita; Syahrul Syahrul; Erma Suryani Sahabuddin; Suryadi Ishak (AL-ISHLAH: Jurnal Pendidikan, 2025)
The implementation of Indonesia’s Merdeka Curriculum requires teachers to adapt to more flexible, student-centered, and competency-based learning approaches. However, teacher readiness remains a major challenge, particularly in non-urban contexts, where limited professional capacity may hinder effective curriculum enactment. This study employed a quantitative, cross-sectional survey design to examine factors influencing teacher readiness for Merdeka Curriculum implementation in public elementary schools in Rilau Ale Subdistrict, Bulukumba Regency. A total of 109 teachers were randomly selected from 25 schools. Data were collected using a validated Likert-scale questionnaire, with reliability coefficients exceeding 0.80 (Cronbach’s alpha). Descriptive statistics and multiple linear regression analyses were used to analyze the data. The findings indicate that teachers’ understanding of the Merdeka Curriculum predominantly falls within low-to-moderate and very low categories, while preparedness in developing instructional materials is largely moderate. Assessment and evaluation competence emerged as the weakest dimension of readiness. Multiple regression analysis revealed that curriculum understanding, instructional material preparation, and assessment competence jointly had a significant effect on teacher readiness (R² = 0.368, p 0.001). These results suggest that teacher readiness is shaped by interconnected cognitive and instructional capacities, while a substantial proportion of variance is influenced by contextual factors beyond the scope of this study. The findings highlight the need for targeted professional development, particularly in assessment literacy and instructional design, to support effective Merdeka Curriculum implementation in non-urban educational settings.